Proses Belajar Perspektif Psikologi Pendidikan Islam - Chabib, Mudzakir; Luthfi, Moh; Rohimah, Siti (Lembaga Yasin AlSys, 2025)
This article provides a comprehensive discussion of the concept of the learning process from the perspective of Islamic educational psychology, in which learning is understood as an activity that results in relatively permanent behavioral changes through experience, practice, and interaction with the environment. These changes encompass three interrelated domains, cognitive (knowledge), affective (attitudes and values), and psychomotor (skills), which collectively shape the learner’s holistic personality. In Islam, learning is not merely an intellectual pursuit but also a spiritual activity regarded as an act of worship and a means of drawing closer to Allah SWT. This aligns with the teachings of the Qur’an and Hadith, which emphasize the obligation of seeking knowledge. Accordingly, Islamic education integrates spiritual and moral dimensions as essential components of learning objectives. Within the framework of Islamic educational psychology, the effectiveness of the learning process is influenced by key factors such as the teacher’s role as a guide, student readiness and motivation, clarity of learning objectives, relevance of content, appropriate instructional methods, supportive learning media, and a fair and objective evaluation system. These elements must be designed in an integrative manner to ensure that the learning process is effective, efficient, and meaningful in accordance with Islamic values. Thus, in Islamic education, the learning process aims not only at achieving academic excellence but also at fostering students’ character and spirituality in a holistic manner.